2003
DOI: 10.1093/jn/133.6.1961s
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplements and Fortification Affect the Risk for Neural Tube Defects, Vascular Disease and Cancer: Evolving Science

Abstract: Folic acid supplements reduce the risk of neural tube defects and may be associated with reduced risk for vascular disease and cancer. Research data from both observational and controlled intervention studies provide strong support for the existing public health policies related to folic acid and neural tube defects. However, educational efforts to promote daily intake of folic acid supplements by women of reproductive age have not, in most cases, resulted in increased supplement use. In contrast, food fortifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(96 citation statements)
references
References 55 publications
1
92
0
3
Order By: Relevance
“…There are possible benefits of increased folate to other groups in the population, in particular for those at risk of vascular disease or some cancers, but these studies provide inconsistent or conditional results. 38 There is uncertainty about possible risks of folate; for instance, in twin genesis 5 (although disputed 39,40 ), in cancer promotion but not genesis 41 and in masking vitamin B12 deficiency 42 (although disputed 29 ). Mandatory fortification does have the advantage of providing a higher intake for women who are unaware of folate or who have an unplanned pregnancy.…”
Section: Food Folate and Physical Activitymentioning
confidence: 99%
“…There are possible benefits of increased folate to other groups in the population, in particular for those at risk of vascular disease or some cancers, but these studies provide inconsistent or conditional results. 38 There is uncertainty about possible risks of folate; for instance, in twin genesis 5 (although disputed 39,40 ), in cancer promotion but not genesis 41 and in masking vitamin B12 deficiency 42 (although disputed 29 ). Mandatory fortification does have the advantage of providing a higher intake for women who are unaware of folate or who have an unplanned pregnancy.…”
Section: Food Folate and Physical Activitymentioning
confidence: 99%
“…The high tHcy serum levels are relatively easy to correct by the use of folic acid at low doses, such as 0.5 mg/day (Oakley et al, 1996), which has been proven cost effective. There is an epidemiological evidence that folic acid supplementation and fortification might protect against the increased risk of neural tube defects, vascular disease and some types of cancer (Bailey et al, 2003;Johnson, 2004;Green and Miller, 2005). Moreover, Verhoef and de Groot (2005) showed that folic acid could be more effective than dietary folate in lowering tHcy concentration.…”
Section: Folate Vitamin B12 and Thcy In Brazilian Newbornmentioning
confidence: 99%
“…This is particularly evident in humans, where the availability of folate for one-carbon metabolism is known to be essential for normal embryonic development, as well having impacts on neural function, cardiovascular disease, alcoholic liver disease, and carcinogenesis (51)(52)(53). It is possible that factors influencing one-carbon activation of H 4 folate, as opposed to H 4 folate availability, may also have clinical relevance.…”
mentioning
confidence: 99%